A A Model For Developing A Cultural Heritage-Driven Learning City To Enhance The Quality Of Life Of Citizens In Nakhon Si Thammarat Municipality - Juntarakote, Benjaporn; Assawasowan, Jutiporn; Rodchareon, Sawimol; Jittham, Pimlapas; Thaboonma, Vayupak; Chaithada, Prakit (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2026)
This research aims to 1) assess the lifelong learning characteristics of citizens, 2) explore how to enhance the quality of life of community learning organizers, 3) develop a model for a cultural heritage-driven learning city, and 4) formulate policy recommendations for the development of the cultural heritage learning city in Nakhon Si Thammarat Municipality. This study employed Participatory Action Research (PAR) integrated with mixed methods, focusing on community-based learning processes involving 30 participants, including local wisdom teachers, community leaders, and key community actors, while assessing both their lifelong learning characteristics and quality of life using the WHOQOL-BREF instrument. The proposed model was developed through a participatory action research process, synthesizing findings from community workshops, in-depth interviews, and stakeholder engagement. Findings highlight the vital role of community leaders in facilitating learning processes and preserving local knowledge. Collaborative learning helped foster continuity and engagement across generations. Participants showed improved quality of life in physical, psychological, social, and environmental domains, with gender and community roles significantly influencing outcomes. Policy recommendations stress the importance of continuity, participatory engagement, intergenerational knowledge transfer, and cross-sector collaboration. The proposed model offers a people-centered approach that can be adapted by other cities aiming to promote sustainable cultural and social development through inclusive learning ecosystems.